Morphological and molecular evidences for the existence of two new species of Homalometron (Digenea: Apocreadiidae), parasites of cichlids (Osteichthyes: Cichlidae) - de León, G. Pérez-Ponce; Razo-Mendivil, U.; García-Magaña, Leticia (Zootaxa, 2012)
Two new species of Homalometron Stafford, 1904 are described, one from the Sinaloan cichlid Cichlasoma beani (Jordan)in the upper Río Santiago basin, Northwestern Mexico, and the other one from the Mayan cichlid Cichlasoma urophthal-mus (Günther) and the Redhead cichlid Vieja synspila (Hubbs) in Southeastern Mexico and Guatemala. Homalometronoctopapillatum n. sp., from the intestine of the Sinaloan cichlid, differs from all congeners by having four pairs of oralpapillae surrounding the mouth and by having vitellaria restricted to the hindbody. In addition, this new species is onlyfound in that species of cichlid, which only occurs in river basins of Northwestern Mexico. The second species,Homalometron mesoamericanum n. sp., was considered to be conspecific with the type species, Homalometron pallidumStafford, in several published accounts on the cichlid parasite fauna of Southeastern Mexico; however, detailed morpho-logical examination of museum specimens as well as freshly collected specimens, along with a comparison through mo-lecular data with H. pallidum from its natural distribution range in North America, allowed us to confirm that thisrepresents, in fact, an undescribed species. The new species is distinguished from other congeners by the combination ofthe following characters: lack of papillae around the mouth opening, the anterior extension of the vitellaria (up to the an-terior border of ovary), two compact eyespots next to pharynx and a large size (1,30–3,19). In this paper we followed anintegrative taxonomy approach in which morphological characters are used in combination with data on two nuclear ribo-somal markers (sequence divergence values and phylogenetic analysis), as well as data on host association and geographic distribution, to give further support to the recognition and description of two new species.